Is inner core seismic anisotropy a marker for plastic flow of cubic iron?. Issue 5 (9th March 2015) - Lincot, A.; Merkel, S.; Cardin, P.
Abstract: This paper investigates whether observations of seismic anisotropy are compatible with a cubic structure of the inner core Fe alloy. We assume that anisotropy is the result of plastic deformation within a large‐scale flow induced by preferred growth at the inner core equator. Based on elastic moduli from the literature, body‐centered cubic or face‐centered cubic Fe produces seismic anisotropy well below seismic observations (<0.4%). A Monte Carlo approach allows us to generalize this result to any form of elastic anisotropy in a cubic system. Within our model, inner core global anisotropy is not compatible with a cubic structure of Fe alloy. Hence, if the inner core material is indeed cubic, large‐scale coherent anisotropic structures, incompatible with plastic deformation induced by large‐scale flow, must be present. Key Points: We build a model where inner core anisotropy is produced by plastic deformation Cubic phases of iron, bcc, or fcc fail to match the global seismic anisotropy The result is generalized to any cubic elasticity by a Monte Carlo approach